90+90+90+x=180

Simple and best practice solution for 90+90+90+x=180 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 90+90+90+x=180 equation:


Simplifying
90 + 90 + 90 + x = 180

Combine like terms: 90 + 90 = 180
180 + 90 + x = 180

Combine like terms: 180 + 90 = 270
270 + x = 180

Solving
270 + x = 180

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-270' to each side of the equation.
270 + -270 + x = 180 + -270

Combine like terms: 270 + -270 = 0
0 + x = 180 + -270
x = 180 + -270

Combine like terms: 180 + -270 = -90
x = -90

Simplifying
x = -90

See similar equations:

| 1.66666666667v+4+0.33333333333v=8 | | 24+(5x-2)=-2(4x-4) | | 6g+1=37 | | 4x-4=4x-7 | | 1/3×3.14×25×9 | | 135/32 | | (3x+1)+3(3x+1)-5=875 | | 68+x+x=180 | | 32/135 | | -7(5+2x)=-49 | | 23+129+x=180 | | 4*ln(7x)=8 | | 2z^2-5z+4=0 | | 500x-13=65x-78 | | 6(-4x+7)-12=-7(2x+7) | | b^3+27= | | m^2x^3+m^9x^2+m^3x^4+m^6= | | 5(7+4x)=155 | | y^2+5y=7 | | 4x+3=9x+33 | | -3x+68-7(x-1)=8x-(2x-2)-6x+3 | | 1.05x=9.020 | | 2n+11=17 | | 3x+39=-69+12x | | -7x+18-7(x-3)=4x-(6x-6)8x+9 | | x^2+10c-25=0 | | 16x+2=8x+6 | | 3b^2+3b-6=0 | | n/3-7=5 | | x/5=181 | | 8/5(-3) | | 3b^2+3b+6=0 |

Equations solver categories